Failure Probability of Three Designs of Zirconia Crowns - Ramos, Gabriela Freitas [UNESP]; Carmona Monteiro, Evelyn Barbosa [UNESP]; Bottino, Marco Antonio [UNESP]; Zhang, Yu; Melo, Renata Marques de [UNESP] (Quintessence Publishing Co Inc, 2015)
This study used a two-parameter Weibull analysis for evaluation of the lifespan of fully or partially porcelain-/glaze-veneered zirconia crowns after fatigue test. A sample of 60 first molars were selected and prepared for full-coverage crowns with three different designs (n = 20): traditional (crowns with zirconia framework covered with feldspathic porcelain), modified (crowns partially covered with veneering porcelain), and monolithic (full-contour zirconia crowns). All specimens were treated with a glaze layer. Specimens were subjected to mechanical cycling (100 N, 3 Hz) with a piston with a hemispherical tip (circle divide = 6 mm) until the specimens failed or up to 2 x 10(6) cycles. Every 500,000 cycles, the fatigue tests were interrupted and stereomicroscopy (10x) was used to inspect the specimens for damage. The authors performed Weibull analysis of interval data to calculate the number of failures in each interval. The types and numbers of failures according to the groups were: cracking (13 traditional, 6 modified) and chipping (4 traditional) of the feldspathic porcelain, followed by delamination (1 traditional) at the veneer/core interface and debonding (2 monolithic) at the cementation interface. Weibull parameters (beta, scale; eta, shape), with a two-sided confidence interval of 95%, were: traditional-1.25 and 0.9 x 10(6) cycles; modified-0.58 and 11.7 x 10(6) cycles; and monolithic-1.05 and 16.5 x 10(6) cycles. Traditional crowns showed greater susceptibility to fatigue, the modified group presented higher propensity to early failures, and the monolithic group showed no susceptibility to fatigue. The modified and monolithic groups presented the highest number of crowns with no failures after the fatigue test. The three crown designs presented significantly different behaviors under fatigue. The modified and monolithic groups presented less probability of failure after 2 x10(6) cycles.